2007
DOI: 10.1007/s12134-007-0004-1
|View full text |Cite
|
Sign up to set email alerts
|

La Diversité Montréalaise à l’Épreuve de la Ségrégation : Pluralisme et Insertion Résidentielle des Immigrants

Abstract: Residential segregation is becoming a complex phenomenon in a great number of cities, in which case, it becomes important to use methodological approaches that allow us to take this complexity into account. This article presents a case study of the Montreal situation using a method describing segregation along five dimensions identified by Massey and Denton (Social Forces 67:281-315, 1988): equality, concentration, aggregation, exposition and centralisation, as well as a set of fifteen segregation indices, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
0
6
0
5
Order By: Relevance
“…The debate about ethnic enclaves that has been raging in Toronto, where at least thirteen ethnic communities of over 100 000 people have enough critical mass to form relatively homogenous spatial concentrations, has no equivalent in Montreal, where ethnic groups are smaller and origins more diverse. Several scholars have shown that Montreal has no ghettos, and although it does have more zones of poverty, these are populated by both immigrants and non-immigrants (Apparicio et al 2007). …”
Section: The Other Turning Up In Unexpected Placesmentioning
confidence: 99%
“…The debate about ethnic enclaves that has been raging in Toronto, where at least thirteen ethnic communities of over 100 000 people have enough critical mass to form relatively homogenous spatial concentrations, has no equivalent in Montreal, where ethnic groups are smaller and origins more diverse. Several scholars have shown that Montreal has no ghettos, and although it does have more zones of poverty, these are populated by both immigrants and non-immigrants (Apparicio et al 2007). …”
Section: The Other Turning Up In Unexpected Placesmentioning
confidence: 99%
“…Certainement, ce processus d'appauvrissement de certains quartiers montréalais semble paradoxal relativement au processus d'installation de l'État-providence (connu comme la Révolution tranquille), qui a transformé le Québec durant la même période. Bien que, comme certains auteurs le soulignent, cette ségrégation économique et ethnique n'ait jamais donné lieu à la formation de « ghettos » dans la ville (Apparicio, Leloup et Rivet, 2007) et qu'elle ait plutôt favorisé la formation d'un espace urbain multiethnique (Radice, 2010), la visibilité accrue de certaines poches d'exclusion a toujours été bien remarquée par les habitants de la ville (Séguin et al, 2012).…”
Section: Montréal-nord Pauvreté Et Gangs De Rueunclassified
“…Not only does the city have a highly ethnically diverse and relatively intermingled, as opposed to segregated, population (Apparicio, Leloup, and Rivet 2007); it also has a complex and sometimes contradictory set of policiesincluding Canada's and Villeray. All four streets are multiethnic, in terms of both their local residential population (according to 2006 census figures) and the range of ethnic affiliations observed in the commercial landscapein signs, storefronts, products and so onbut each has its own special multiethnic mix.…”
Section: Street-corner Cosmopolitanism In Montréalmentioning
confidence: 99%